Pulmonary Birefringent Material in Fatal Heroin Overdose - Akyıldız, Elif Ülker; Ersoy, Gökhan; Özata, Ahmet Bülent; Çelik, Safa (The Bulletin of Legal Medicine, 2005)
Fatal heroin overdose is one of the major preventable causes of deaths. The mechanism of death for fatal heroin overdose has not been adequately explained yet. The noncardiogenic pulmonary edema is the most striking finding. On the other hand, lungs may exhibit granulomatous reactions in chronic abuse. In this study, histopathological cross-sections taken from the lungs of heroin intoxication overdose cases, whose previous postmortem examinations of the cases had been performed at the Mortuary Department of the Council of Forensic Medicine, were reevaluated. Twenty medicolegal cases without known heroin abuse history were evaluated as control group. The specimens were examined under polarizing light and foreign bodies were encountered in 15 of the 86 cases.Key words: Heroin, lung, foreign body, biréfringent material
Keywords: heroin; lung; foreign body; birefringent material